Semen characteristics, semen discard rate and fertility in Murrah buffalo bulls - KANCHAN; SINGH, NARINDER (The Indian Journal of Animal Reproduction, 2023)
A total of 2747 collections from 24 buffalo bulls were evaluated to find the per cent semen discard at the time of semen collection and also during freezing process. Bulls were categorized into three semen discard groups; low (30-50%), medium (50-70%) and high (70-90% ). The various parameters viz. age at first collection, body weight at first collection, average semen volume, pre and post-freezing discard, initial motility, post-thaw motility and conception rate were studied among these groups to find the effect of di scard rate on fe rtility of Murrah buffalo bulls. The mean values of various parameters viz. age at first collection (months), body weight at first collection (kg), average semen volume (ml), pre-freezing discard (%) and post-freezing discard (% ), initial motility (%), post-thaw motility (%) and conception rate (%) were 27.2±1.37, 386.50±21.06; 3.47±0.14, 32.41±2.87, 29.30±2.26, 57.37:tl.06, 42.71±0.81 and 29.36±2.15, respectively. The results have shown that the age and weight of bulls at sexual maturity were lowest in high semen discard group (22.9±2.88 months and 347.5±45.17 kg). The mean value of age and body weight at first collection, average semen volume, pre-freezing semen discard and conception rate did not vary significantly among three discard groups. The results indicate that conception rate of bulls is not effected by discard rate of semen. Post-freezing discard was significantly higher (Ps().01) in high discard group as compared to other discard groups. Initial motility and post-thaw motility of semen was signifo.antly higher (Ps().01; P 0.05) in low discard group as compared to medium and high discard groups. The results indicated that the studies on semen discard rate would help to identify bulls with minimum discard rate with best semen characteristics for selection in breeding programme to meet the semen production targets for genetic improvement of this species.